Seguimiento farmacoterapéutico en pacientes con lupus eritematoso sistémico atendidos en un hospital de Iquitos 2022 - Montes Yaicate, Milagros (2024)
Systemic Lupus Erythematosus is considered one of the most prevalent diseases, affecting women between 15 and 40 years of age, since in recent years there has not been enough impact on the study of this disease, so its diagnosis is carried out based on to pharmacotherapeutic compliance. Objective: Determine the effect of pharmacotherapeutic monitoring on therapeutic adherence in patients with systemic lupus erythematosus seen in the rheumatology clinic of Hospital III-Iquitos, EsSalud, 2022. Methodology: The study was quantitative, descriptive, cross-sectional and prospective. Population: The size of the study population was 57 patients and the sample was 47 patients with systemic lupus erythematosus. Results: through the sociodemographic characteristics sheet, Pharmacotherapeutic Follow-up sheet (SFT), Morisky Green Therapeutic Adherence Test and Sheet Visual Analogue Pain Scale (VAS) the following data was obtained: age of 27 - 59 years with 80.9%, female sex with 91.5% and 51.1% were married and the origin was in Iquitos with 53.2%, in the category of Safety was predominant in PRM 6 with 38.3%, therapeutic adherence with 55.3% and the intensity of moderate pain was obtained at 76.6%. Conclusion: The research work provided a contribution to future research for diseases such as systemic lupus erythematosus, considered an autoimmune disease.